Implementasi Manajemen Mutu Dan Keselamatan Pasien di Klinik Komunitas: Studi Kualitatif - Mohammad Labib; Inne Indraaryani Suryaalamsah; Abdullah A Afifi (Journal of Regional Development and Technology Initiatives, 2026)
Patient safety is a key component of quality management systems in healthcare services. At the primary healthcare level, the implementation of patient safety systems often faces various challenges, such as limited human resources, organizational culture, clinical leadership, and suboptimal incident reporting systems. Community clinics play a strategic role in providing safe, effective, and high-quality healthcare services for the community. This study aims to examine the implementation of quality management and patient safety at the Baitul Qurro School Clinic. It also seeks to identify barriers and supporting factors in the implementation of patient safety, as well as to explore the experiences of healthcare workers in implementing service quality systems. This research employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observation of service processes, and review of the clinic’s quality documents. The research informants consisted of healthcare workers and clinic managers involved in patient care and quality management. Data analysis was conducted using thematic analysis to identify key themes related to organizational structure, service processes, and patient safety outcomes. The results show that the implementation of patient safety is influenced by several key factors, including leadership commitment, the availability of standard operating procedures, communication among healthcare workers, and the incident reporting system. Limited resources and the lack of structured training were identified as barriers to the optimal implementation of patient safety systems. This study highlights the importance of strengthening the patient safety culture at the primary healthcare level through the integration of quality management systems, capacity building for healthcare workers, and the reinforcement of professional ethical values based on Al-Islam and Kemuhammadiyahan.